Pre-Treatments Of Sago Fiber For Ethanol Fermentation - Janggu, U.; Bujang, K.B. (2009)
The efficiency of different pre-treatment methods on dried sago fiber: steaming, alkaline boiling followed by suspending in diluted acid and alkaline boiling followed by boiling in diluted acid - prior to enzymatic hydrolysis was studied. The effects of pre-treatments in the separated liquid and solid fractions along with its degree of convertibility were examined. Steaming was shown to be the most effective method for preparation of sago fiber prior to enzymatic hydrolysis, producing relatively high recovery of solid fraction (50.6%), cellulose content (38%) with high convertibility degree of fiber (42%), high lignin reduction (6%) and significant concentration of starch (12.8 g/L) in the liquid fraction upon filtration. The results of pretreatment using alkaline was lower at 21.3%, 51%, 2% and 3.3g/L when suspended in diluted acid and at 19%, 49%, 3% and 0.1g/L when boiled in diluted acid, for recovery of solid fraction, cellulose content, lignin reduction and starch content, respectively.